Transcriptome Profiling and Cytological Assessments for Identifying Regulatory Pathways Associated With Diorcinol N-Induced Autophagy in A3 Cells - Xiao-Long Yuan; Xiu-Qi Li; Xiu-Qi Li; Kuo Xu; Xiao-Dong Hou; Zhong-Feng Zhang; Lin Xue; Xin-Min Liu; Peng Zhang (Frontiers Media S.A., 2020)
Fungal secondary metabolites serve as a rich resource for exploring lead compounds with medicinal importance. Diorcinol N (DN), a fungal secondary metabolite isolated from an endophytic fungus, Arthrinium arundinis, exhibits robust anticancer activity. However, the anticancer mechanism of DN remains unclear. In this study, we examined the growth-inhibitory effect of DN on different human cancer cell lines. We found that DN decreased the viability of A3 T-cell leukemia cells in a time- and concentration-dependent manner. Transcriptome analysis indicated that DN modulated the transcriptome of A3 cells. In total, 9,340 differentially expressed genes were found, among which 4,378 downregulated genes and 4,962 upregulated genes were mainly involved in autophagy, cell cycle, and DNA replication. Furthermore, we demonstrated that DN induced autophagy, cell cycle arrest in the G1/S phase, and downregulated the expression of autophagy- and cell cycle-related genes in A3 cells. By labeling A3 cells with acridine orange/ethidium bromide, Hoechst 33,258, and monodansylcadaverine and via transmission electron microscopy, we found that DN increased plasma membrane permeability, structural disorganization, vacuolation, and autophagosome formation. Our study provides evidence for the mechanism of anticancer activity of DN in T-cell leukemia (A3) cells and demonstrates the promise of DN as a lead or even candidate molecule for the treatment of acute lymphoblastic leukemia.